Combining Organic Fertilizer With Controlled-Release Urea to Reduce Nitrogen Leaching and Promote Wheat Yields - Yang, Xiuyi; Zhang, Chao; Ma, Xiaoli; Liu, Qianjin; An, Juan; Xu, Shujian; Xie, Xingyuan; Geng, Jibiao (Frontiers in Plant Science, 2021)
The soil deterioration, low nitrogen use efficiency (NUE) and environmental risks caused by excessive chemical N fertilizer use are key factors restricting sustainable agriculture. It is extremely critical to develop effective N management strategies that consider both environmental and agronomic benefits. From 2017 to 2019, a field experiment was conducted to assess the effects of combinations of organic fertilizers (OF, provided at 30%, 50% and 70% of the total applied N) and controlled-release urea (CU) on the NUE, N leaching and wheat yield compared with urea and CU. The results suggested that OF released N slowly in the early stage and showed a significant residual effect, while CU released N quickly in the first 2 months. The OF substitutes with 30–50% CU increased wheat yield by 4.16–9.17%, while the 70%OF+30%CU treatment showed no significant difference relative to the urea treatment. The average maximum apparent NUE recovery (50.42%) was achieved under the 50%OF+50%CU treatment, but the partial factor productivity was not affected by the N type. As the OF application rate increased, the total carbon content increased and total N value decreased. The NO3--N and NH4+-N concentrations in the OF+CU treatments were lower before the jointing stage but higher from the grain-filling to mature stages, than urea treatment. NO3--N and NH4+-N were mainly concentrated in the 0–60-cm layer soil by OF substitution, and N leaching to the 60–100-cm soil layer was significantly reduced. Hence, the results suggest that the combination of 30–50%OF with CU synchronizes absorption with availability due to a period of greater N availability in soils, proved to be the best strategy for simultaneously increasing wheat production and reducing N leaching.